Nurses' perception of thirst in patients within palliative home care: a qualitative study - Caroline Lythell; Anne Söderlund Schaller; Tiny Jaarsma; Maria Friedrichsen (BMC, 2024)
Abstract Background Thirst is the body's natural urge to replenish fluids in response to a deficiency in hydration. Patients at the end of life gradually lose their independence and reach a point where they become unable to express their needs and can no longer drink on their own. In palliative care, the main advice is to provide regular oral care to relieve symptoms such as dry mouth and thirst. However, according to previous studies the prevalence of thirst and dry mouth remains. Aim The aim of this study was to describe palliative care, nurses' views and experiences of thirst in end-of-life care in specialist palliative care units. Methods A qualitative interview study with an inductive approach was conducted. Eighteen nurses working in six different specialist palliative care units in different hospitals in Sweden were interviewed. The interviews were transcribed and analysed with a content analysis approach according to Graneheim and Lundman. Results When nurses discuss thirst, they perceive thirst as a problem for the patient. This is attributable to various factors, including the patient breathing with an open mouth, a reduced level of awareness, and negligence on the part of the nursing staff. Signs of thirst are dry mouth, and frequently and intense sucking on the oral care stick during oral care. It also emerged that not all nurses perceived that dying patients experienced thirst. They believe that thirst is something that is reduced in the dying patient in the same way as hunger. The most important thing to them is to relieve the dry mouth by providing good oral care. Several issues, such as a lack of guidelines paired with the patient's reduced consciousness and hence his/her lack of communication, make assessing thirst problematic. Conclusion Nurses have different thoughts and experiences about thirst, where some perceive patients as thirsty while others perceive them as having a dry mouth. Nurses expressed that both evidence and guidelines are lacking.